"There's no playbook for when your kid has cancer": Desired elements of an electronic resource to support pediatric cancer communication. Issue 3 (5th January 2023) - Greenzang, Katie A.; Scavotto, Madison L.; Revette, Anna C.; Schlegel, Sarah F.; Silverman, Lewis B.; Mack, Jennifer W.
Abstract: Introduction: Acute lymphoblastic leukemia (ALL), the most common childhood malignancy, has a relatively favorable long‐term prognosis. Yet the complexity of treatment and the emotionality of the diagnosis leave families feeling unprepared for many aspects of therapy. This qualitative study aimed to identify desired elements and format of a communication resource to support patients and families facing a diagnosis of ALL. Methods: Semi‐structured interviews of 12 parents of children receiving ALL treatment, 10 parents of survivors of ALL, and eight adolescent and young adult (AYA) survivors of ALL were conducted between February and June 2021. The interviews focused on communication experiences throughout treatment and identified domains to be addressed in a resource in development. Results: All participants supported the development of an interactive, electronic health (eHealth) resource to help navigate ALL treatment. They felt a website would be helpful in addressing information gaps and mitigating pervasive feelings of overwhelm. Participants specifically sought: (a) information resources to address feelings of cognitive overload; (b) practical tips to help navigate logistical challenges; (c) clear depictions of treatment choices and trajectories to facilitate decision‐making; and (d) additional psychosocial resources and support. Two overarching themes that families felt should be interwoven throughout the eHealth resource were connections with other patients/families and extra support at transitions between phases of treatment. Conclusions: A new diagnosis of ALL and its treatment are extremely overwhelming. Patients and families unanimously supported an eHealth resource to provide additional information and connect them with emotional support, starting at diagnosis and extending throughout treatment.